2017
DOI: 10.1002/suco.201600019
|View full text |Cite
|
Sign up to set email alerts
|

Bond of deformed steel reinforcement in lightweight foamed concrete

Abstract: Low weight and thermal insulating properties make lightweight foamed concrete (LWFC) an attractive substitute for normal‐weight concrete (NWC). The unfamiliarity and paucity of design guidance challenge the structural use of LWFC. One concern is the bond of steel reinforcement in LWFC. This paper presents the results of pull‐out bond tests and beam‐end bond tests. The parameters were a reference NWC and LWFC with densities of 1,200, 1,400, and 1,600 kg/m3 and rebar diameters of 10, 12, and 20 mm with embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 14 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…The bond failure models include split and pull‐out. When the depth of the concrete protective layer exceeds a certain range ( c / d > 5–6) or it comes to hooped specimens, the failure model of bond between the deformed bar and the concrete is generally the shearing off of concrete keys between adjacent ribs, which is the main focus of this study. This paper has established the relationship between bond stress and the slip surface.…”
Section: Introductionmentioning
confidence: 99%
“…The bond failure models include split and pull‐out. When the depth of the concrete protective layer exceeds a certain range ( c / d > 5–6) or it comes to hooped specimens, the failure model of bond between the deformed bar and the concrete is generally the shearing off of concrete keys between adjacent ribs, which is the main focus of this study. This paper has established the relationship between bond stress and the slip surface.…”
Section: Introductionmentioning
confidence: 99%
“…Interlock between steel ribs and concrete is highly dependent on the concrete strength (density of foamed concrete), bar diameter and ribs geometry. Tests performed by Villers [6] have shown that lightweight foamed concrete of 1200 kg/m 3 density ensures more than eight time lower bond strength than normal concrete based on similar mixture receipt. Poor bond behaviour of cellular concrete is associated with low fracture and stiffness causing premature crushing of concrete by steel ribs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a low‐water–cement ratio of magnesium phosphate cement equates to a low‐binder–sand ratio and weak bonding strength with Portland cement . The addition of fly ash approximates the color of magnesium phosphate cement specimens to the color of Portland cement, thus reducing the cost of material, enhancing the fluidity of mortar, and reducing its bonding strength . However, repaired concrete is frequently eroded by acid rain, industrial wastewater, and other corrosive media during usage.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] The addition of fly ash approximates the color of magnesium phosphate cement specimens to the color of Portland cement, thus reducing the cost of material, enhancing the fluidity of mortar, and reducing its bonding strength. [19][20][21] However, repaired concrete is frequently eroded by acid rain, industrial wastewater, and other corrosive media during usage. In addition, the hydration of cement is eroded and thus damaged by corrosive ions.…”
Section: Introductionmentioning
confidence: 99%